Total Knee Arthroplasty for Knee Osteoarthritis: Support for a Foregone Conclusion?. Issue 2 (July 2017) - Steinhaus, Michael E.; Christ, Alexander B.; Cross, Michael B.
Total knee arthroplasty (TKA) is generally accepted as the definitive treatment for advanced knee arthritis after patients fail nonoperative treatments; however, the safety and efficacy of TKA compared to continued nonoperative treatment has never been proven in high-quality, randomized controlled trials. Recently, a 2015 Danish study published a 12-month follow-up on a cohort of patients randomized to either a TKA or continued nonsurgical management for advanced knee osteoarthritis (OA). The authors reported significantly greater improvement in the TKA group in functional outcome scores such as the overall Knee Injury and Osteoarthritis Outcome Score (KOOS4 score), the KOOS subscales, EQ-5D descriptive index, and timed get up-and-go and 20-m walk tests; however, patients in the TKA did suffer significantly more serious adverse events (SAE). The authors concluded that TKA combined with additional nonoperative care postoperatively is more efficacious than nonsurgical treatment alone in terms of improving pain, function, and quality of life at 12 months but is associated with more SAE. The purpose of this review is to identify the strengths and weaknesses of this trial, interpret its outcomes within the context of prior literature, and evaluate the validity of its conclusions.